Assessment of Patients’ Concerns and Misconceptions Regarding Periodontal Treatment in a Tertiary Care Dental Hospital: A Cross-Sectional Study - Aditi Vivek Gosavi; Agraja Patil; Shardool Jagtap; Renuka Jawal (Oral Sphere Journal of Dental and Health Sciences, 2026)
Introduction: The pathophysiology of periodontal disease depends mainly on the attitude of the patients towards their oral health. Many patients avoid treatment due to perceived barriers. Aim of the study is to assess concerns and misconceptions of patients indicated for definitive periodontal treatment. Methodology: A digital close ended questionnaire was designed to seek responses in a dichotomous format to streamline and facilitate data collection. Data analysis was done by the same digital format. Results: The study showed that out of 200 patients interviewed by the Investigators, major impediment was the notion of treatment being time consuming and many follow ups for maintenance of the periodontal health. Some of the misconceptions included post treatment loss of teeth, loosening of teeth among others. Conclusion: It can be concluded that by increasing the awareness among the patients about maintenance of their periodontal health and the available treatment plans, they can be encouraged to seek periodontal intervention at the appropriate time.